Experimental and numerical investigation into pile spacing effects on the dynamic response of coastal pile foundation bridges considering current-wave-earthquake forces - Riyadh Alsultani; Ibtisam R. Karim; Saleh I. Khassaf (Advances in Bridge Engineering)
Abstract Pile spacing significantly influences the dynamic response of coastal pile foundation bridges, particularly under complex loading conditions. This study presents a novel methodology for optimizing the distribution of piles within a nine-pile cap and evaluates the effects of varying pile spacings on the dynamic fluid-structure interaction. An experimental investigation was conducted to assess the dynamic response of three scaled bridge specimens with pile spacings of 2.5D, 2.0D, and 1.5D (where D is the pile diameter) under combined current-wave forces during seismic events. The acceleration and displacement responses were measured using the innovative Reality Water Structure Earthquake Interaction Test (RWSEIT) system. The results revealed that reduced pile spacing (1.5D) led to a significant increase in both acceleration and displacement responses, indicating higher vulnerability under dynamic loading. In contrast, wider spacing (2.5D) demonstrated improved stability, with reduced displacement and acceleration, thereby enhancing the overall structural resilience. The analysis also highlighted the critical role of water depth, current velocity, and wave properties in modulating the dynamic response. Complementary 3D numerical models were developed using the Finite Element DIANA Software, and the numerical results closely matched the experimental findings, thereby validating the model’s accuracy. These insights contribute to more sustainable infrastructure design, aligning with global efforts to enhance the resilience and longevity of coastal structures while minimizing environmental impact. These findings provide crucial insights into the fluid-structure interactions of coastal bridges, offering practical guidance for the design and assessment of deepwater pile foundations under seismic and hydrodynamic forces.